Temporal interactive response is resistant to cloudy ocular media in the slow double-stimulation multifocal electroretinogram. Issue 7 (16th February 2012) - Ho, Wing-Cheung; Chu, Patrick H W; Ng, Yiu-Fai; Tong, Patrick P C; Woo, Victor C P; Chan, Henry H L
Abstract : Aim: To examine the influence of cloudy media on the slow double-stimulation multifocal electroretinogram (mfERG). Methods: Slow double-stimulation mfERG responses were measured from 26 subjects with normal ocular health under normal and light scattering conditions (induced using acrylic sheets) (Experiment 1) and another nine cataract patients before and after cataract surgery (Experiment 2). The amplitudes and implicit times of the first (M 1 ) and second (M 2 ) stimulation were compared under normal and light scattering conditions in Experiment 1 and they were compared under precataract and postcataract surgery in Experiment 2. Results: Compared with control conditions (normal and postcataract surgery), the M 1 amplitude in the central region was significantly reduced in light scattering conditions (acrylic sheets and precataract surgery); the M 2 amplitude and both M 1 and M 2 implicit times of all regions examined were moderately affected in precataract surgery. The M 1 :M 2 amplitude ratio and implicit time ratio were virtually unaffected in cloudy media for either central or mid-peripheral regions. Conclusion: Cloudy media affects the mfERG amplitude and implicit time in the slow double-stimulation, but does not affect the response ratio (ie, M 1 :M 2 amplitude ratio and implicit time ratio) between the two stimulations. This suggests that the ratio analysis can be applied in patients with mild to moderately cloudy ocular media to evaluate the functional integrity of the retina.